Pregnancy and Toxoplasmosis: should screening be a routine practice? - Esra Cinar Tanriverdi; Hakan Uslu; Yasemin Cayir; Zulal Ozkurt (SERNEV, 2019)
Because infectious agents can reach the fetus throughthe placenta, pregnancy is regarded as a particular period for contagiousdiseases. Identification of infections during pregnancy and appropriatetreatment can prevent fetal disorders. For this purpose, to avoid their harmfuleffects on fetus and newborn, various infectious diseases are screened duringpregnancy. Toxoplasma gondii infection in pregnancy is transmitted through thetransplacental pathway leading to severe neurological sequelae such as fetalabortion, stillbirth, intrauterine growth retardation, cranial calcifications,blindness, deafness, and mental retardation. This can lead to serious socialand economic problems for the family and the infant, as well as society. Toprevent these sequelae, infections during pregnancy need to be identified andappropriately treated. There are different opinions and practices in the worldregarding the screening of T. gondii during pregnancy follow-up. This reviewaimed to assess the seroprevalence of T. gondii infection during gestation inTurkey and the world, its effects on the fetus, ways of protection, andsuggestions about screening in the world and in Turkey in light of theliterature, so that this becomes a guide for clinical practice for physicians.